Social Aspects in National Public Procurement - Szymańska, Anna; Szymanski, Jarosław (Journal of Finance and Financial Law, 2025)
The purpose of the article. Public procurement, which was originally aimed solely at reducing corruption, has been expanded to include additional elements that can have a broad impact on the socio-economic environment. One of these elements is social aspects, which can broaden the scale of effects obtained from the implementation of the order. The aim of the work is to quantitatively examine the changes taking place in the public procurement market in the use of social aspects, including social clauses. The study was conducted to confirm a growing interest in this element of procurement among public entities. The paper hypothesizes that in the years 2017–2023 there was a significant increase in the use of new procurement opportunities using social aspects. The research question is whether the lack of measurable incentives for contracting authorities limits the introduction of social aspects in public procurement. Methodology. The paper discusses the principles of classifying social aspects of public procurement in years 2017–2023, taking into account social clauses in particular. The empirical part uses aggregated data obtained from documents published by the Public Procurement Office. In order to enable comparability of observations in individual years, an indicator analysis was used. Since data for 2024 was not available in official reports, the research was conducted on the basis of a 200-element random sample taken from all public procurements awarded by domestic entities in that year. Results of the research. Analysis of published aggregated market data and data obtained from the sample taken indicate a limited increase in the use of social aspects in public procurement. Despite the even incidental use of social clauses, it can be stated that the situation in this area is gradually improving, as the average annual rate of change in the period under review showed a 16% increase in the number of such orders and a 33% increase in their value.